Directing successful projects with PRINCE2 - Office of Government Commerce (OGC) (London : TSO (The Stationery Office), 2009)
Suitable for senior managers and project board members, this handbook describes how to oversee projects being managed using PRINCE2. It sets PRINCE2 in the wider context of project management and also describes or cross-references techniques which support the PRINCE2 method.
"OGC official product" --cover.
Includes bibliographical references and index.
oif 21/05/2014
Loans
Keywords: Project management; PRINCE2 (Computer file); Management information systems; Industrial project management; PRINCE2 .; Project management--Business.; Business; United Kingdom